The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/children9020133
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioral Effects of Montessori Pedagogy on Children’s Psychological Development and School Learning

Abstract: This review examines the quantitative behavioural studies that have evaluated the effects of Montessori pedagogy on children’s psychological development and school learning. The analyses of only three “Randomized Controlled Trials—RCT” studies published to date reveal varied and contradictory effects. Firstly, these findings are discussed in the light of several methodological limitations: the absence of active control groups, small sample sizes, diversity of measures, or lack of control over the implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Bahatheg (2010) examined the effect of the Montessori Method on creative problem-solving skills in a study conducted in a preschool with 24 students and put forth that there were significant differences between groups in terms of problem-solving capacities. Also, Gentaz and Richard (2022) concluded that the problem-solving skills of children who were educated with the Montessori approach were higher than those who received traditional education. Lyman and Foyle (1988) explained the importance of using the cooperative learning method in preschools and the first years of elementary school.…”
Section: Discussionmentioning
confidence: 99%
“…Bahatheg (2010) examined the effect of the Montessori Method on creative problem-solving skills in a study conducted in a preschool with 24 students and put forth that there were significant differences between groups in terms of problem-solving capacities. Also, Gentaz and Richard (2022) concluded that the problem-solving skills of children who were educated with the Montessori approach were higher than those who received traditional education. Lyman and Foyle (1988) explained the importance of using the cooperative learning method in preschools and the first years of elementary school.…”
Section: Discussionmentioning
confidence: 99%
“…So that educators no longer feel strange about certain behaviors of children and cannot understand children, and then cooperate with children and "enjoy" these "sensitive periods" together with children." [8]…”
Section: Grasp the Child's Sensitive Periodmentioning
confidence: 99%
“…Ayuste y Trilla (2005) se refieren a ellas como p edagogías transformadoras, puesto que -a diferencia de la educación tradicional-se orientan a la transformación del individuo y su contexto social, a partir de una mirada crítica de la sociedad contemporánea y sus modos de funcionamiento. Sin embargo, las pedagogías alternativas aún no cuentan con evidencia sólida suficiente para certificar su éxito educativo (Gentaz y Richard, 2022;Martín-Sánchez, 2021), lo que sugiere la necesidad de más investigación. Hoy en día, esto adquiere mayor relevancia a la luz de la Pandemia de COVID 19 que significó, especialmente durante 2020, largos períodos de cuarentena con clases online, afectando la calidad de vida de muchos estudiantes, su salud mental y su bienestar (Liang, 2020).…”
Section: Introductionunclassified